(untitled) (Huellas, 2020)
In the last decades, various changes on the environment implied socio-productive transformations and certain practices on the territory, which negatively affected artisanal fishing. This article analyzes the territorialities of artisanal fishermen in the Paraná Delta in the period 2012-2017, to understand the experiences, the meanings on the territory and the way of exercising their territoriality in interaction with other subjects. A qualitative methodology is applied, which is based on the analysis of secondary sources, as well as interviews and field work observations carried out. Finally, it is shown that the concept of “territorial practices” allows for an understanding of the physical and symbolic barriers that fishermen encounter to develop their activity before various actors.